Indigenous public policies: state domination (Research, Society and Development, 2021)
Indigenous peoples have suffered a relationship of domination since the colonial period. Such domination occurred, initially, on the part of the Catholic Church, which had the responsibility for the catechization of the indigenous people. Then, domination becomes the responsibility of the State, responsible for institutionalizing or legitimizing rights, but also duties to society, which may or may not take into account the socio-cultural peculiarities of indigenous communities when formulating public policies. It is observed that, even if there are indigenous public policies, they are either poorly designed or insufficient, so that, many times, they contribute to the extinction of the differences between the indigenous peoples themselves and between these and non-indigenous peoples, since they their cultural, territorial, educational, multi-ethnic, health, self-determination, rights are not respected. Therefore, the objective of this research was to identify the characteristics observed in the relationship between the State and the indigenous populations in their interface with public policies. To this end, a narrative literature review was carried out in which the following were highlighted: the management cycle and the specificity of public policies in the indigenous reality; the cultural, social and economic nuances of indigenous peoples in their interaction with the State; and a synthesis of the dialogues and conflicts of the State and society (indigenous people) in relevant public policies for this social group. As a result, zero or low participation of indigenous peoples was identified in various stages of the flow of public policy, while they seek greater insertion in the political-administrative process.